Nutri-garden for Sustainable Food Security and Nutritional Diversity in Hamirpur District of Bundelkhand Region (U.P.) - Kumari, Phool; Mustaf, Md; Somvanshi, S.P.S.; Singh, Chanchal; Kumar, Prashant; Shalini, (Indian Journal of Extension Education, 2019)
Nutri-garden is one of the easiest ways of ensuring access to a healthy diet that contains adequate macro and micronutrients. Thus the study were planned keeping in view improved food security, increased availability of vegetables, better nutrition and food diversity by provisioning bio-fortified vegetable varieties seeds and saplings. The purposive experimental study was planned. The study was conducted in 12 villages under FLDs programme in Hamirpur District. Total 120 farm families were selected for the study having area around 150 m2 near the house. Total 33 varieties were provided throughout the year in every Nutri-garden. Brocalli, Pusa Chaulai, Sarson Saag, and Kasuri Menthi etc. (rich source of nutrients) were first time introduced in selected Nutri-Garden. It was found that area available for kitchen garden in most of farm families was cultivated area near the house (29.17%) and unused land near the house (35.83%). It was observed that maximum production was in Rabi season followed by Kharif and Zaid season respectively, may be due to scarcity of water in Bundelkhand region during summer. Availability of Macro and micro nutrients through consumption of vegetables in daily routine diet was found satisfactory.
Keywords: Food security; Nutritional diversity; Malnutrition; Mitigation; Nutri-garden